Factors affecting translation of addressing terms from English into VietNamese / Lê Thị Nhung; GVHD: TS. Hồ Ngọc Trung - Lê, Thị Nhung
The study use descriptive and contrastive analysis methods to point out: the Vietnamese translation equivalents of English ATs, factors affecting the translation of addressing terms from English into Vietnamese. The implication of the study would propose some pedagogical implications for teaching in a broader sense, covering the field of addressing terms betweenmembers in the communities. The study also raised the need for translators of English-Vietnamese literary texts, especially in treating terms of addressing terms, to pay close attention to the linguistic and cultural elements of the source texts.